Source apportionment, ecological and health risks of potentially toxic elements in street dusts across different land uses in city of Kermanshah, Iran - Ali Asgari; Soheil Sobhanardakani; Mehrdad Cheraghi; Bahareh Lorestani; Maryam Kiani Sadr (Scientific Reports)
Abstract In this study, the contamination, ecological and human health risks as well as source apportionment of As, Cd, Co, Cr, Cu, Mn, Ni, Pb, Zn, and V in street dusts of different land-uses in Kermanshah, Iran were investigated. A total of 192 dust samples were taken from 16 sites and were analyzed for their elemental contents using ICP-OES. The computed mean values for the geo-accumulation index (I-geo) and the pollution index (PI) ranged from − 6.07 to 2.67 and from 0.023 to 9.58, respectively, indicating ‘unpolluted’ to ‘moderately to heavily polluted’, and ‘slight to very high polluted’ pollution levels, respectively. The pollution load index (PLI) with a cumulative mean value of 1.03 reflected moderate pollution levels across the entire study area. Moreover, the ecological risk (RI) of 135 indicated moderate ecological risks throughout the study region. The mean hazard index (HI) values for the analyzed potentially toxic elements (PTEs) for both adults and children were all within the safe limit (< 1). Furthermore, the total carcinogenic risk (TCR) values showed that the carcinogenic risks associated with As, Cd, Cr, and Ni for both target populations were at tolerable to unacceptable levels. The positive matrix factorization (PMF) model identified traffic emissions and sources, fossil fuel combustion and natural sources, and industrial emissions as the major sources of tested elements. Hence, a thorough investigation into the sources of ecological health risks associated with dust contamination from potentially toxic elements (PTEs) is recommended for future studies.